Teachers and educational policies: Negotiating discourses of male role modelling. (October 2017) - Moreau, Marie-Pierre; Brownhill, Simon
Abstract: Since the 1990s there has been some considerable discussion in English education policy of boys' underachievement and of male teachers serving as 'role models'. Drawing on two separate research projects, this article explores the diverse ways in which individual teachers negotiate discourses of role modelling, while also considering the performative nature of these discourses and some of their effects on teachers. The article shows that discourses of role modelling retain some currency among teachers and highlights the need for contemporary research on equality issues to inform the work of both policy-makers and teachers. Highlights: This article explores how teachers negotiate role modelling discourses in England. Discourses of role modelling have become more subdued in policy and media circles. However, they retain some currency, including among teachers. Teachers take up and negotiate these discourses in various ways. Several effects of these discourses on teachers are identified.